EmergencyFire - An Ontology for Fire Emergency Situations - Bitencourt, Kattiuscia; Durão, Frederico; Mendonça, Manoel (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
The emergency response process is quite complex since there is a wide variety of elements to be evaluated for taking decisions. Uncertainties generated by subjectivity and imprecision affect the safety and effectiveness of actions. The aim of this paper is to develop an ontology for emergency response protocols, in particular, to fires in buildings. This developed ontology supports the knowledge sharing, evaluation and review of the protocols used, contributing to the tactical and strategic planning of organizations. The construction of the ontology was based on the methodology Methontology. The domain specification and conceptualization were based in qualitative research, in which were extracted 131 terms with definitions, of which 85 were assessed by specialists. From there, in the Prot´eg´e tool, the domain’s taxonomy and the axioms were created. The specialists validated the ontology using the assessment by human approach (taxonomy, application and structure). Thus, a sustainable ontology model to the rescue tactical phase was ensured.